17-β-estradiol increases cytosolic free calcium concentrations ([Ca2+]i) of endothelial cells and modulates the responses to acetylchoune - (:unkn) unknown (My University, 1996)
In this study, acute effects of E2 addition on ([Ca2+)i) of human umblical vein endothelial cell (HUVEC) cultures were measured by fura-2 fluorescence. E2 was added subsequently at 10-9-10-6M concentrations to HUVEC cultures, which were either deprived of eslrogens or preincubated with E2 for 24 h. In both groups of cultures E2 stimulated dose dependent significant increases in [Ca2+]i at concentrations 10-9-10-6M with the means 48.2, 76.2, 120.0, 129.4% in E2 deprived group and 28.1, 43.9, 56.7, 58.9% in E2 preincubated group, compared to basal levels. Incubation of cells with tamoxifen did not effect the response to E2. Performing experiments in Ca2+ free/EGTA buffer yielded transient increases in [Ca2+]i suggesting release of Ca2+ from intracellular stores first. Inhibition of the influx pathway by addition of La3+ at the peak of the Ca2+ response immediately reduced [Ca2+], to basal levels. Addition of carbachol (10°, 107M) to cultures deprived of estrogens did not induce increases in [Ca2+], but after incubation of the same cultures with E2 for 30 min., carbachol addition caused significant increases in [Ca2+]i with the means 56.9, 93.4% compared to basal levels respectively, while cultures which were incubated with E2 for 24 h responded to carbachol directly in similiar amounts. Results of the study show that E2 may modulate the functions of endothelial cells directly in short time and also indicate that E2 may be necessary for the response to acetylcholine especially at low concentrations and may explain the mechanism of acute E2 effects in potentiation of endothelium dependent vasodilation in response to acetylcholine.